Proprotein Convertase Subtilisin/Kexin Type 9 and Inflammation: An Updated Review - Wu, Na-Qiong; Shi, Hui-Wei; Li, Jian-Jun (Frontiers in Cardiovascular Medicine, 2022)
The function of Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9), a novel plasma protein, has mainly been involved in cholesterol metabolism in the liver, while, more interestingly, recent data have shown that PCSK9 also took part in the modulation of inflammation, which appeared to be another explanation for the reduction of cardiovascular risk by PCSK9 inhibition besides its significant effect on lowering lower-density lipoprotein cholesterol (LDL-C) concentration. Overall, a series of previous studies suggested an association of PCSK9 with inflammation. Firstly, PCSK9 is able to induce the secretion of proinflammatory cytokines in macrophages and in other various tissues and elevated serum PCSK9 levels could be observed in pro-inflammatory conditions, such as sepsis, acute coronary syndrome (ACS). Secondly, detailed signaling pathway studies indicated that PCSK9 positively regulated toll-like receptor 4 expression and inflammatory cytokines expression followed by nuclear factor-kappa B (NF-kB) activation, together with apoptosis and autophagy progression. Besides, PCSK9 enhanced and interacted with scavenger receptors (SRs) of inflammatory mediators like lectin-like oxidized-LDL receptor-1 (LOX-1) to promote inflammatory response. Additionally, several studies also suggested that the role of PCSK9 in atherogenesis was intertwined with inflammation and the interacting effect shown between PCSK9 and LOX-1 was involved in the inflammatory response of atherosclerosis. Finally, emerging clinical trials indicated that PCSK9 inhibitors could reduce more events in patients with ACS accompanied by increased inflammatory status, which might be involved in its attenuating impact on arterial plaque. Hence, further understanding of the relationship between PCSK9 and inflammation would be necessary to help prevent and manage the atherosclerotic cardiovascular disease (ASCVD) clinically. This review article will update the recent advances in the link of PCSK9 with inflammation.